(untitled) - Wilson, H. James (Boston, Massachusetts, 2018)
Artificial intelligence (AI) is transforming how we work right now. Are you ready? In the past, robots were typically large pieces of machinery, sectioned off from human workers to perform precise, mechanical tasks on an assembly line. But now, bots and other AI technologies go far beyond this in augmenting human capabilities--not just robots on the factory floor of an auto plant, but algorithms in the back office of a healthcare insurer and chatbots interacting with retail customers. Unlike any software tool or service that's come before, artificial intelligence has the power to profoundly change the very nature of work itself--and this is happening in all kinds of enterprises and across all functions of the organization.
Keywords: Đổi mới công nghệ,Technological innovations